THE EFFECT OF ENTREPRENEURSHIP AND E-COMMERCE ON MARKETING PERFORMANCE WITH AGILITY AS INTERVENING VARIABLE - Nurcholis, Lutfi; Suhendi, Chrisna; Utami, Luci Delayani (Universitas Brawijaya, Indonesia, 2022)
This study aims to give the research gap solution by adding agility as the intervening variable on the relationship between entrepreneurship and e-commerce with marketing performance. The population in this study is the owner or manager of Muslim Clothing SMEs in Central Java. The number of samples used by 100 respondents for data collection using a questionnaire. The data analysis used is Partial Least Squares (PLS). The study results reveal that entrepreneurship, e-commerce, and agility have a significant influence on marketing performance. Agility was proven as an intervening variable on the relationship between entrepreneurship and e-commerce with marketing performance. SMEs can improve marketing performance through entrepreneurship and e-commerce and will be more effective if done by SMEs through agility. This paper suggests that the next researcher increase the population and sample of Muslim Fashion SMEs in another area.Â